The Influence of Fatigue on Star Excursion Balance Test Performance in Dancers. Issue 3 (September 2018) - Armstrong, Ross; Brogden, Christopher Michael; Milner, Debbie; Norris, Debbie; Greig, Matt
Dance is associated with a high risk of injury and fatigue is often a contributing factor. The Star Excursion Balance Test (SEBT) has been used to identify alterations in normal movement that may contribute to injury risk; however, there has been limited investigation of the potential effects of fatigue. The aim of this study was to explore the influence of dance-specific fatigue on SEBT performance, with implications for injury and performance in dance. Thirty-five university dancers completed the modified SEBT in anterior, posterolateral, and posteromedial directions prior to and immediately following the Dance Aerobic Fitness Test (DAFT). The SEBT was completed for dominant and non-dominant legs. Heart rate and rate of perceived exertion were quantified as measures of fatigue. Post-DAFT, the mean SEBT percentage maximized reach distances for dominant and non-dominant legs were non-significant compared to pre-DAFT scores. Lack of a main effect for exercise was observed in each of the anterior dominant and non-dominant, posterolateral dominant and non-dominant, and posteromedial dominant and non-dominant scores. It is concluded that the limited changes in the ability of dancers to perform the SEBT suggest that they were able to maintain SEBT performance in both dominant and non-dominant legs following exercise. This resistance to fatigue may demonstrate a dance-specific performance adaptation so that potential alterations in movement performance that may increase injury risk were not observed.